Fiscal fatigue and public debt limit in Brazil: Are we on sustainable path? - Rodrigo Mendes Pereira (Institute for Applied Economic Research (ipea), 2020)
In this paper I use Ghosh et al. (2013) approach to assess Brazil's fiscal sustainability, fiscal fatigue, and public debt limit. Using monthly data for the last 21 years, I estimate Brazil's fiscal reaction function and an eventual fiscal fatigue effect, which is a lack of government's will (or capability) to implement higher primary surpluses as a reaction to higher levels of debt. I show that fiscal fatigue occurs at relatively mild levels of debt in Brazil. I also define Brazil's debt limit, which is the precise level of debt/GDP ratio above which the debt dynamics becomes explosive, public debt becomes unpayable, and the government invariably defaults. I show that the debt limit in Brazil is much lower than the limits that have been estimated for advanced economies.
Keywords: C22; E62; H63; 330; primary balance; debt/GDP ratio; fiscal fatigue; debt limit